Strengthening village governance: A qualitative study of transparency, accountability, and participation in village fund management in Tappale Village, Libureng Subdistrict, Bone Regency - Andi Rahmat Nizar Hidayat (Department of Government Science, 2025)
This research aims to analyze the implementation of transparency, accountability, and community participation in Village Fund management in Tappale Village, Libureng Subdistrict, Bone Regency. Employing an in-depth case study approach, this research explores the mechanisms, levels, and challenges in realizing good governance at the village level. Data were collected through semi-structured interviews with village government officials, members of the Village Consultative Body , community leaders, and general residents, as well as through observation and document analysis. The findings reveal that despite formal efforts to implement governance principles, the implementation still faces significant obstacles related to information accessibility, the effectiveness of accountability mechanisms, and the level of inclusive community participation. This study concludes that strengthening Village Fund governance requires an approach that goes beyond formal compliance, emphasizing community empowerment, capacity building of local actors, and the development of participatory and accountable mechanisms. These findings provide practical implications for village governments and recommendations for future research in the effort to achieve more effective Village Fund management and contribute to sustainable village development.